Combined Effect of Levels in Personal Self-Regulation and Regulatory Teaching on Meta-Cognitive, on Meta-Motivational, and on Academic Achievement Variables in Undergraduate Students - de la Fuente, Jesús; Sander, Paul; Martínez-Vicente, José M.; Vera, Mariano; Garzón, Angélica; Fadda, Salvattore (Frontiers in Psychology, 2017)
The Theory of Self- vs. Externally- Regulated LearningTM (SRL vs ERL) proposed different types of relationships among levels of variables in Personal Self-Regulation (PSR) and Regulatory Teaching (RT) to predict the meta-cognitive, meta-motivational and meta-emotional variables of learning, and of Academic Achievement in Higher Education. The aim of this investigation was empirical in order to validate the model of the combined effect of low-medium-high levels in PSR and RT on the dependent variables. For the analysis of combinations, a selected sample of 544 undergraduate students from two Spanish universities was used. Data collection was obtained from validated instruments, in Spanish versions. Using an ex-post-facto design, different Univariate and Multivariate Analyses (3x1, 3x3 and 4x1) were conducted. Results provide evidence for a consistent effect of low-medium-high levels of PSR and of RT, thus giving significant partial confirmation of the proposed rational model. As predicted, (1) the levels of PSR and positively and significantly effected the levels of learning approaches, resilience, engagement, academic confidence, test anxiety, and procedural and attitudinal academic achievement; (2) the most favorable type of interaction was a high level of PSR with a high level RT process. The limitations and implications of these results in the design of effective teaching are analysed, to improve university teaching-learning processes.